Demyelinating disorders of the central nervous system in childhood - Chabas, Dorothee; Waubant, Emmanuelle L. (New York : Cambridge University Press, 2011)
'Although multiple sclerosis and other disorders of myelin formation and repair are most commonly associated with adults, they can also occur in infants, children and adolescents. Up to 5 percent of those with MS experience symptoms before the age of 18, and the number of cases diagnosed is rising. There is a lack of awareness about these diseases in childhood, however, even amongst pediatric neurologists and MS specialists. Demyelinating Disorders of the Central Nervous System in Childhood provides comprehensive coverage of these diseases, highlighting throughout the differences between management in childhood and in adults. With sections dedicated to the diagnosis, course, treatment and biology of pediatric MS, detailed chapters on other childhood demyelinating diseases, including acute disseminated encephomyelitis, optic neuritis, acute complete transverse myelitis and neuromyelitis optica, are also provided. Essential reading for pediatric neurologists and MS specialists, this book will also be valuable reading for adult neurologists and pediatricians'--Provided by publisher.
ADEM: 17. Clinical and biological features of Acute Disseminated Encephalomyelitis Jin S. Hahn and Silvia Tenembaum; 18. Magnetic Resonance Imaging of Acute Disseminated Encephalomyelitis Russell C. Dale and Esther Tantsis; 19. Treatment and prognosis of ADEM Marc Tardieu and Amy T. Waldman; Part V. Optic Neuritis in Children: 20. Pediatric optic neuritis Amy T. Waldman and Laura J. Balcer; 21. Recurrent isolated optic neuritis in the pediatric population Bianca Weinstock-Guttman and Grant T. Liu; Part VI. Acute Complete Transverse Myelitis in Children: 22. What is acute transverse myelitis (ATM) in children? Frank S. Pidcock and Guillaume Sire; Part VII. Neuromyelitis in Children: 23. Neuromyelitis optica in children Andrew McKeon and Timothy Lotze; Index.
Keywords: Multiple sclerosis; Adolescent; Child; Demyelinating Autoimmune Diseases, CNS; Diagnosis, Differential; Encephalomyelitis; Infant; Optic Neuritis